واقع عملية إدارة المخاطر في شركات التأمين السورية - عكروش, محمد; قضماني, عادل; حسن, رانيا (Latakia University Journal - Economic and Legal Sciences Series, 2019)
Risk in insurance industry is a real fact, and most of insurance companies are working under risk and uncertainty, but in different and varying degrees. Risk management (RM) plays a pivotal role in addressing and handling these various risks. Based on the above, this research came mainly to study and assess the reality of risk management in the insurance companies operating in Syria. We followed the descriptive study (survey) in this research based on the problem of the study and objectives it seeks to achieve. The study population included all insurance companies operating in Syria. The researcher used a questionnaire specifically designed to assess risk management maturity by (Ciorciari & Blattner, 2007), and the questions have been adapted with the Syrian environment. The findings of this study show that there is a marked decrease in the level of maturity of the project risk management in the insurance companies operating in Syria, where the maturity level is located within the first level, which does not meet the minimum requirements of the risk management process in these companies. The reason for this is the absence of risk management culture among high-level management and therefore workers. This low level of maturity is a major threat because it keeps many risks unknown and therefore unknown effects and consequences. يعد الخطر في صناعة التأمين حقيقة قائمة وأغلب الشركات تتعرض له ولكن بدرجات مختلفة ومتفاوتة. تلعب إدارة المخاطر دوراً محوريا في عملية معالجة هذه المخاطر، انطلاقاً مما سبق جاء هذا البحث بشكل أساسي بهدف دراسة وتقييم واقع عملية إدارة المخاطر في شركات التأمين العاملة في سورية. تمَّ إتباع المنهج الوصفي في الدراسة استناداً إلى المشكلة والأهداف التي تسعى إلى تحقيقها، وشمل مجتمع الدراسة كافة شركات التأمين العاملة في سورية. تم جمع البيانات باستخدام استبانة مصممة خصيصاً لقياس مستوى نضج إدارة المخاطر وذلك بالاعتماد على الأداة من قبل (Ciorciari & Blattner, 2007) وتمَّ تكييف الأسئلة مع البيئة. تَبَيَّنَ مِنْ خلال الدراسة بأنه يوجد انخفاض ملحوظ في مستوى نضج إدارة المخاطر في شركات التأمين العاملة في سورية، حيث يقع مستوى النضج ضمن المستوى الأول والذي لا يلبي أدنى احتياجات عملية إدارة المخاطر في هذه الشركات، والسبب في ذلك برأي الباحثة يعود إلى غياب ثقافة إدارة المخاطر لدى الإدارات وبالتالي العاملين، الأمر الذي يعد تهديداً كبيراً لأنه يبقي القسم الأكبر من المخاطر مجهولاً وبالتالي آثاره ونتائجه مجهولة.